Amantadine-assembled nanostimulator enhances dimeric RBD antigen-elicited cross-neutralization against SARS-CoV-2 strains. (April 2022) - Zhang, Ye; Wang, Ruixin; He, Chunyan; Zhang, Yu-Fang; Luo, Zhongrui; Luo, Jia; Chen, Sisi; Jin, Yu; Xie, Bowen; Liu, Ye
Highlights: Developing a new nanostimulator to enhance dimeric RBD-elicited cross-neutralization against SARS-CoV-2 strains. Verifying that amantadine-assembled nanostimulator (AAS) enhances host immunity by RIG-I-like receptor signaling pathway. Highlighting the convenience and robustness of AAS application. Graphical Abstract: Amantadine-assembled nanostimulator (AAS) activates RIG-I-like receptor signaling pathway to enhance dimeric RBD antigen-elicited cross-neutralization against different SARS-CoV-2 strains. ga1 Abstract: There is an urgent need to develop new vaccination strategies to elevate the cross-neutralization against different SARS-CoV-2 strains. In this study, we construct the spherical amantadine-assembled nanostimulator (AAS). Amantadine as immunostimulating molecules are displayed on the outermost layer of AAS. Molecular mechanism analysis reveals that AAS can activate RIG-I-like receptor (RLR) signaling pathway to increase the expression of type I interferons in vivo . AAS-mediated activation of RLR signaling pathway further promotes the maturation and proliferation of dendritic cells (DCs) and T helper cells (Ths), finally activating B cells to produce potent antibody responses. In performance evaluation experiments, the mixture of AAS and dimeric RBD significantly enhances RBD-specific humoral responses (4-fold IgG, 3.5-fold IgG2a, 3.3-fold IgG2b, 3.8-fold IgG3 and 1.3-fold IgM), in comparison to aluminum adjuvant-assistant dimeric RBD. Importantly, AAS dramatically elevates dimeric RBD-elicited cross-neutralization against different SARS-CoV-2 strains such as Wuhan-Hu-1 (9-fold), B.1.1.7 (UK variant, 15-fold), B.1.351 (South African variant, 4-fold) and B.1.617.2 (India variant, 7-fold). Our study verifies the mechanism of AAS in activating RLR signaling pathway in host immune system and highlights the power of AAS in improving antigen-elicited cross-neutralization against different SARS-CoV-2 strains.